Inequality by population groups and income sources: Accounting for inequality changes in Spain during the recession - Carlos Gradín (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
I discuss a new approach which decomposes inequality into the contributions of population groups by income sources. I estimate a matrix with rows and columns which indicate different population groups and income sources respectively, with each element indicating the marginal change in the inequality contribution of a group (as measured by the recentered influence function) when an income source is added and with all contributions adding up to overall inequality. The approach can be used to analyse the contributions of groups and sources to the trend in inequality over time (or between distributions), disentangling the effect of changes in the composition of the population by groups and changes in their income distribution by sources. An empirical application characterizes the distributional change in Spain following the Great Recession, defining population groups based on household labour market attachment, with disposable income sources including gross primary income, social benefits, and direct taxes. The results show that the increase in inequality can, to a large extent, be attributed to a compositional effect, with rising market income inequality driven by the massive increase in unemployment, which is only partially compensated for by the higher equalizing effect of social protection through different population groups. This trend partially reversed after 2014. The analysis also identifies important distributional changes.
Keywords: D31; D63; H24; J64; 330; decomposition; Great Recession; inequality; income sources; population groups; Spain